Students’ Competence in Using Transitive and Intransitive Verbs in Simple Sentences - Zuhesty Raitah Mansur; Sutaryo Sutaryo; Firmansyah Firmansyah; Yetty Yetty (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to investigate students’ competence in using transitive and intransitive verbs in simple English sentences and to identify the types of errors commonly made by students. A quantitative descriptive research design was employed, using multiple-choice and essay tests as research instruments. The participants were 30 third-semester students of Class A from the English Language Education Study Program, Khairun University. The findings revealed that the average student score was 69.17, which falls within the “Enough” or medium competence category. The results also indicated that students demonstrated better mastery of transitive verbs compared to intransitive verbs. The most frequent errors involved the use of inappropriate objects after intransitive verbs and confusion in distinguishing verbs that can function as both transitive and intransitive. A comparative analysis between the two test formats showed that students performed better in essay tests than in multiple-choice tests, with 63.3% of students achieving a “Very Good” category in applying verbs in contextual sentences. These findings highlight the need for focused instructional strategies to enhance grammatical competence, particularly in understanding and applying verb types accurately in sentence construction. The study contributes to the broader understanding of English grammar acquisition among EFL learners and provides insights for curriculum improvement in language education programs.